THE INSTITUTE OF EMERGENCY ARBITRATOR - Bliuvaitė, Marija (Teisė, 2015)
The article analyses the function of an emergency arbitrator to impose interim measures of protection in arbitration. Before the establishment of this institute, a party, aiming to impose interim measures of protection since court of arbitration has not been formed, had an opportunity to apply to competent national court. The established insitute of emergency arbitrator offered an opportunity to apply for interim relief to arbitration institution together with the claim or before filling the claim. It resulted in an autonomous process with the merits of arbitration, such as confidentiality and economy. Although there was a meaningful step towards trully independent arbitral procedure, some disputable questions are still left. Firstly, it is not clear how should decisions on damages, information of the other party, etc. be made when considering interim relief in an emergency case. Secondly, the question of variety of measures that can be imposed by emergency arbitrator remains as well as the enforcement of each such measure. What is more, the proper procedure for the appointment of emergency arbitrator during a very short period of time is a demanding challenge for arbitration institution. Due to the abovementioned aspects, national court still sometimes is a more desirable alternative for emergency relief. However, the institute of emergency arbitrator indicates the positive movement in the field of civil procedure law and is open for further developments. Legislation in Lithuania allows to address the request for interim measures both to emergency arbitrator and national court as long as it does not become abuse of procedural rights.